The value of drug-induced sleep computed tomography in diagnosis of obstructive sleep apnea syndrome: a pilot study. (3rd October 2019) - Zhang, Xiaoman; Lv, Ning; Li, Xin; Sun, Shasha; Li, Jianfeng; Yang, Huiming; Yu, Zhaoyan; Wang, Haibo
Abstract: Background: Obstructive sleep apnea syndrome (OSAS) is a public health problem that affects a large amount of people. Surgery sometimes is considered a better treatment modality that does not require the use of a device such as CPAP. Objectives: To explore the value of anesthetic-induced sleep computed tomography (DI-SCT) in the diagnosis of OSAS. Materials and methods: A total of 124 patients with OSAS aged between 18 and 65 years old were enrolled in this study. The upper airway was scanned by computed tomography (CT) while they were wake and went sleep. Sleep was induced by dexmedetomidine under electrocardiograph and oxyhemoglobin saturation monitoring. Parameters relevant to OSAS were then collected and counted. Results: CT scanning revealed that 119 occurred stenosis in oropharynx, in which 5 cases were accompanied with stenosis or occlusion at retroglossal area. About 38 (30.67%) cases existed deviation of nasal septum with retropalatal problems. About 61.33% of patients had multi-level obstructions and the most common obstructive site was oropharynx (90.67%). Conclusions and significance: DI-SCT is a safe and non-invasive modality for diagnosing the obstructive sites in OSAS patients.